Evaluation of Probiotic Properties and Safety of Enterococcus faecium Isolated From Artisanal Tunisian Meat “Dried Ossban” - Zommiti, Mohamed; Cambronel, Mélyssa; Maillot, Olivier; Barreau, Magalie; Sebei, Khaled; Feuilloley, Marc; Ferchichi, Mounir; Connil, Nathalie (Frontiers in Microbiology, 2018)
Enterococcus faecium strains were isolated from an original biotope, artisanal dried Tunisian meat ‘Dried Ossban’ and evaluated for safety and capacity as probiotics. Gram-positive, catalase negative and bacteriocin-producing bacteria were screened using selective microbiological media. All isolates were identified by phenotypic and molecular tools. Five E. faecium strains (MZF1, MZF2, MZF3, MZF4 and MZF5) were selected and further assessed for their probiotic properties. They were found to be resistant to the physiological concentrations of bile salts, and the harsh conditions of the gastrointestinal tract, and showed autoaggregation and adhesion ability. All these isolates possess at least one enterocin and could efficiently inhibit the growth of L. innocua HPB13. The analysis of their safety profile, revealed for almost all the strains, absence of cytotoxicity and virulence determinants, and susceptibility to clinically important antibiotics such as vancomycin. These data suggest that these bacteria, isolated from ‘Dried Ossban’, do not present a risk to human health, and may be considered as interesting candidates for future use as probiotics and bioprotective cultures for application in the food and/or feed industries.